ChemInform Abstract: Metal‐Supported Catalysts Encapsulated in Mesoporous Solids: Challenges and Opportunities of a Model Concept. Issue 36 (15th August 2013) - Gruenert, Wolfgang; Gies, Hermann; Muhler, Martin; Polarz, Sebastian; Lehmann, Christian W.; Grossmann, Dennis; van den Berg, Maurits; Tkachenko, Olga P.; De Toni, Andrea; Sinev, Ilya; et al., et al.
Abstract Review: 39 refs.